2022
DOI: 10.1021/acs.inorgchem.2c00486
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Aqueous Synthesis of Porous Hollow PdCu Alloy Nanoparticles for Enhanced Ethanol Electrooxidation

Abstract: Bimetallic PdCu porous hollow nanoparticles (PHNs) with hierarchical nanostructures and well-alloyed compositions were precisely synthesized through a one-pot aqueous synthetic route. Bimetallic PdCu PHNs exhibited multiple enhancement synergies and thus performed well in ethanol oxidation electrocatalysis with remarkable activity and stability. This work expedites rational design and synthesis of the high-hierarchy alloy electrocatalysts for fuel cell electrocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The PdM did not reveal any peaks for pure metals (i.e., Pd, Au, Mn, and Cu) or their oxides, which implies the formation of pure Pd alloys with highly ordered nanostructures in line with reports elsewhere. 45,46 This is further proved by the small-angle XRD of the PdM nanostructures with an intense diffraction at 2θ (∼0.11°), assigned to the {111} facet of Pd crystals (Figure S3a). These peaks also are resolved for the commercial Pd/C catalyst, but with a slight shift toward lower 2θ values for the PdM nanocrystals.…”
Section: Physical Characterizationmentioning
confidence: 64%
“…The PdM did not reveal any peaks for pure metals (i.e., Pd, Au, Mn, and Cu) or their oxides, which implies the formation of pure Pd alloys with highly ordered nanostructures in line with reports elsewhere. 45,46 This is further proved by the small-angle XRD of the PdM nanostructures with an intense diffraction at 2θ (∼0.11°), assigned to the {111} facet of Pd crystals (Figure S3a). These peaks also are resolved for the commercial Pd/C catalyst, but with a slight shift toward lower 2θ values for the PdM nanocrystals.…”
Section: Physical Characterizationmentioning
confidence: 64%
“…For the coupled system of cost-effective and widespread application, anodic EOR catalysts with high efficiency, stability, and selectivity are required. To date, noble metals such as Pt and Pd are still the state-of-the-art candidates for EOR, but they suffer from high cost, reaction intermediate poisoning, and sluggish kinetics in EOR. An effective strategy to overcome these challenges is to alloy the noble metals with certain metals such as Cu, Ag, Au, and Pb. Our recent work revealed that Sb as an adatom in the branched PdSb alloy not only modifies the electronic nature of Pd active sites but also participates the electrocatalysis reaction itself, thus enhancing the EOR activity . Previous works also demonstrated that the introduction of the Bi atom into Pd can facilitate the removal of carbonaceous intermediates in the EOR process and thus improve the stability for electrocatalytic reactions. Despite that tremendous studies have been made to produce multimetallic alloys to maximize the EOR performance, the Pd-based catalysts with both Sb and Bi incorporation have rarely been paid to simultaneously increase the EOR activity and stability. …”
Section: Introductionmentioning
confidence: 99%
“…Direct ethanol fuel cells (DEFCs) involve reactions between ethanol oxidation at the anode and oxygen reduction at the cathode. Both of the reactions need high-efficiency electrocatalysts that can enhance electrocatalytic performance for practical application of DEFCs. Especially, the anode reaction that electrochemically oxidizes ethanol is of big significance owing to high energy and power density (see eqs 1–5 in Figure S1 for EOR pathways). So far, palladium (Pd) is still the most used electrocatalyst for the electrocatalytic ethanol oxidation reaction (EOR). A possible route to enhance EOR performance is the fabrication of Pd-based alloys with 3d metals (such as Au, Ag, Cu, Ni, etc. ). Alloying 3d metals can optimize the electronic structure of Pd, thus weakening the adsorption of poisoning intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the anode reaction that electrochemically oxidizes ethanol is of big significance owing to high energy and power density (see eqs 1–5 in Figure S1 for EOR pathways). So far, palladium (Pd) is still the most used electrocatalyst for the electrocatalytic ethanol oxidation reaction (EOR). A possible route to enhance EOR performance is the fabrication of Pd-based alloys with 3d metals (such as Au, Ag, Cu, Ni, etc. ). Alloying 3d metals can optimize the electronic structure of Pd, thus weakening the adsorption of poisoning intermediates. Very recently, nonmetals, for example, P and S, have also been alloyed into Pd-based nanocrystals. In addition to the optimized electronic structure, nonmetals also facilitate the adsorption of OH species (OH ads ) of Pd catalysts and consequently accelerate the oxidation removal of poisonous species during EOR electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%